1997
DOI: 10.1002/(sici)1097-4628(19971024)66:4<609::aid-app1>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of flourine-containing polyimides

Abstract: A series of new fluorine-containing polyimides have been synthesized from the condensation of 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2-bis[4-(4-aminophenoxy)phenyl] -1,1,1,3,3,3 -hexafluoropropane, or 2,2 -bis[4 -(4 -amino -2 -trifluoromethylphenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane with various aromatic dianhydrides. The dielectric constant at 1 KHz in the fluorine-containing polyimides decreases from 3.51 to 2.72 as fluorine content increases. The poly(amic acid)s had inherent viscosities of 0.52-1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
2

Year Published

2000
2000
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 4 publications
1
34
2
Order By: Relevance
“…2,2-Bis(4-hydroxyphenyl)hexafluoropropane (6F-bisphenol-A; Acros), 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (mp 132-133 C, II a ), 24 1,2-bis(4-amino-2-trifluoromethylphenoxy)benzene (mp 116-117 C, II b ), 25 4,4 0 -bis(4-amino-2-trifluoromethylphenoxy)biphenyl (mp 155-156 C, II c ), 12 4,4 0 -bis(4-amino-2-trifluoromethylphenoxy)-3,3 0 ,5,5 0 -tetramethylbiphenyl (mp 256-257 C, II d ), 26 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]propane (mp 131-132 C, II e ), 27 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane (mp 65-66 C, II f ), 28 9,9-bis[4-(4-amino-2-trifluoromethylphenoxy)-phenyl]fluorene (mp 239-240 C, II g ), 29 4,4 0 -bis(4-aminophenoxy)biphenyl (mp 137-138 C, II f , Chriskev) were used as received. Commerially available aromatic dianhydrides including PMDA (Lancaster), BTDA (Acros), and ODPA (Chriskev) were recrystallized from acetic anhydride before use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,2-Bis(4-hydroxyphenyl)hexafluoropropane (6F-bisphenol-A; Acros), 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene (mp 132-133 C, II a ), 24 1,2-bis(4-amino-2-trifluoromethylphenoxy)benzene (mp 116-117 C, II b ), 25 4,4 0 -bis(4-amino-2-trifluoromethylphenoxy)biphenyl (mp 155-156 C, II c ), 12 4,4 0 -bis(4-amino-2-trifluoromethylphenoxy)-3,3 0 ,5,5 0 -tetramethylbiphenyl (mp 256-257 C, II d ), 26 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]propane (mp 131-132 C, II e ), 27 2,2-bis[4-(4-amino-2-trifluoromethylphenoxy)phenyl]hexafluoropropane (mp 65-66 C, II f ), 28 9,9-bis[4-(4-amino-2-trifluoromethylphenoxy)-phenyl]fluorene (mp 239-240 C, II g ), 29 4,4 0 -bis(4-aminophenoxy)biphenyl (mp 137-138 C, II f , Chriskev) were used as received. Commerially available aromatic dianhydrides including PMDA (Lancaster), BTDA (Acros), and ODPA (Chriskev) were recrystallized from acetic anhydride before use.…”
Section: Methodsmentioning
confidence: 99%
“…9,10 Among the six kinds of commercially available aromatic dianhydrides including pyromellitic dianhydride (PMDA), 3,3 0 ,4,4 0 -benzophenone-tetracarboxylic dianhydride (BTDA), 3,3 0 ,4,4 0 -biphenyltetracarboxylic dianhydride (BPDA), diphenylsulfone-3,3 0 ,4,4 0 -tetracarboxylic dianhydride (DSDA), 4,4 0 -oxydiphthalic dianhydride (ODPA) and 6FDA, the polyimides were deriving from ODPA or 6FDA with aromatic diamines showed lighter color than others. The reason was proposed that polyimides containing ether chains [11][12][13] or hexafluoroisopropylidene group 9,14 could reduce the CTC formation of polymer. Therefore, we synthesized the bis(ether anhydride) containing ether chains and hexafluoroisopropylidene group, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]hexafluoropropane dianhydride (I), and produced a series of lightly-colored poly(ether imide) films with various aromatic diamines.…”
mentioning
confidence: 99%
“…12 Fluorination is also known to enhance the solubility and optical transparency of polyimides. [13][14][15] Therefore, it is expected that fluorinated polyimides will be widely applied in electro-optical and semiconductor industries.…”
Section: Introductionmentioning
confidence: 99%
“…12 Fluorination is also known to enhance the solubility and optical transparency of polyimides. [13][14][15] Therefore, it is expected that fluorinated polyimides will be widely applied in electro-optical and semiconductor industries.Recent studies demonstrated that polyimides derived from ether-bridged aromatic diamines with trifluoromethyl (3F) groups, such as 1,3-or 1,4-bis(4-amino-2-trifluoromethylphenoxy)benzene, are soluble and high temperature polymer materials with low dielectric constant, high optical transparency, † To whom correspondence should be addressed. and low birefringence.…”
mentioning
confidence: 99%
“…13 Fluorination is also known to enhance the solubility and optical transparency and to lower moisture absorption of polyimides. [14][15][16] Therefore, it is expected that fluorinated polyimides will be widely applied in electro-optical or semiconductor industries. Recent studies have demonstrated that polyimides derived from ether-bridged aromatic diamines with a trifluoromethyl (3F) group are generally soluble with low moisture uptakes, low dielectric constants, high optical transparency, and low birefringence.…”
mentioning
confidence: 99%